Pelatihan deteksi dini kanker payudara pada masyarakat dan kader Posbindu PTM di RW 8 Kelurahan Air Putih Kecamatan Tampan Kota Pekanbaru - Tuti Restuastuti; Viviyanti Viviyanti; Ridha Restila; Ilhami Romus (Unri Conference Series: Community Engagement, 2019)
Breast cancer is the most frequent cancer among women. WHO data states that in 2018 an estimated 627,000 women die from breast cancer or approximately 15% of all cancer deaths among women. However, the survival of patients with breast cancer is quite high when detected early. Posbindu PTM RW 08 Air Putih is a posbindu guided by FK UNRI to prevent and control non-communicable diseases, including breast cancer. Therefore, increasing the ability of Posbindu PTM cadres to conduct BSE socialization (Self Breast Examination) is necessary. The form of community service is BSE training in the community and Posbindu PTM cadres. In addition, participants were facilitated for examinations by specialist doctors. The activity was attended by 16 participants, beginning with the material about Posbindu PTM, breast cancer, BSE practice and screening for participants who have symptoms of breast cancer. Evaluation of activities was assessed by active participation and community response to the question and answer session. Participants can also re-practice BSE. The results of the examination of three participants who were examined by a doctor, suspected (suspect) 1 person FAM, 1 person Carcinoma mammae, and 1 other person did not. The suspected participants were suggested to immediately conduct a clinical examination and ask the RW to help them obtaining BPJS.